Parâmetros quantitativos da resistência parcial à Phakopsora pachyrhizi medidos em cultivares de soja - Serafini, Pablo Tuzi (2019)
The increase in food production has been one of the major subjects driving the debates about human progress. Currently, due its potential to human and animal feeding, soybean crop is one of the most important agricultural commodities worldwide. In Brazil, the soybean production system has developed considerably in the past four decades, enabling remarkable gains on crop yield over this period. Nevertheless, soybean crop has faced several hinders in the pursuit of higher yields potential, with especial attention to the occurrence of fungal diseases, especially Asian Soybean Rust (ASR) (Phakopsora pachyrhizi Sydow), a highly damaging disease to this crop. Numerous strategies may be applied to ASR management, among them the use of less susceptible cultivars has been recommended as economic viable and more environmentally sustainable alternative, furthermore it may be a complementary technique to contribute to other practices such as chemical control. This study aimed to assess soybean cultivar reaction to P. pachyrhizi. To do so, two field trials were carried out in the 2016/17 and 2017/18 crop seasons with 76 and 92 soybean crop cultivars, respectively. The parameters evaluated were rust severity, number of uredines and lesions cm-2, rust progress rate and area under rust progress curve. The results were submitted to variance analyses and the principal component analysis. The cultivars were clustered through the K-means method into groups accordingly to the similarity of the assessed parameters. Yet, a third experiment was carried out under greenhouse conditions where 92 cultivars were sown aiming to estimate the mean latent period of P. pahyrhizi in the same materials grown in field conditions. A greater number of assessments enabled a better discrimination of the cultivars through estimating the rust progress rate. The greater cultivar differentiation has occurred in the assessments under the middle epidemic outbreak. Cultivars presenting greater partial resistance showed lower rust progress rate, especially during the grain filling period, influencing the disease intensity at the end of the crop cycle.